Electromagnetic theory for microwaves and optoelectronics . (2nd ed.) - Zhang, Keqian (Springer, 2017)
"This book is a first year graduate text on electromagnetic fields and waves. At the same time it serves as a useful reference for researchers and engineers in the areas of microwaves and optoelectronics." "Following the presentation of the physical and mathematical foundations of electromagnetic theory, the book discusses the field analysis of electromagnetic waves confined in material boundaries, or so-called guided waves, electromagnetic waves in the dispersive media and anisotropic media. Gaussian beams and scalar diffraction theory. The theories and methods presented in the book are foundations of wireless engineering, microwave and millimeter wave techniques, optoelectronics and optical fiber communication."--Jacket.